2013
DOI: 10.2131/jts.38.547
|View full text |Cite
|
Sign up to set email alerts
|

(–)-Xanthatin induces the prolonged expression of c-Fos through an <i>N</i>-acetyl-L-cysteine (NAC)-sensitive mechanism in human breast cancer MDA-MB-231 cells

Abstract: -We reported that (-)-xanthatin, a xanthanolide sesquiterpene lactone present in the Cocklebur plant, exhibited potent anti-proliferative effects on human breast cancer cells, in which GADD45γ, a novel tumor suppressor gene, was induced. Mechanistically, topoisomerase IIα (Topo IIα) inhibition by (-)-xanthatin was shown to be the upstream trigger that stimulated the expression of GADD45γ mRNA and concomitantly produced reactive oxygen species (ROS) to maintain this expression. Since the anticancer drug etoposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…β-Actin was used as a housekeeping gene for RT-PCR. (B) A working model of (-)-xanthatin-produced cell death signaling was described in combination with previous findings (Takeda et al, 2011(Takeda et al, , 2013a(Takeda et al, , 2013b. As shown in the Figure, (-)-xanthatin inhibits the catalytic activity of Topo IIα, which is coupled with the concomitant production of ROS; GADD45γ, which is up-regulated by DNA damage, may be an execution factor in cell death.…”
Section: Resultsmentioning
confidence: 81%
See 3 more Smart Citations
“…β-Actin was used as a housekeeping gene for RT-PCR. (B) A working model of (-)-xanthatin-produced cell death signaling was described in combination with previous findings (Takeda et al, 2011(Takeda et al, , 2013a(Takeda et al, , 2013b. As shown in the Figure, (-)-xanthatin inhibits the catalytic activity of Topo IIα, which is coupled with the concomitant production of ROS; GADD45γ, which is up-regulated by DNA damage, may be an execution factor in cell death.…”
Section: Resultsmentioning
confidence: 81%
“…The results obtained showed that among members of the Rho family comprising RhoA, RhoB, and RhoC (Wheeler and Ridley, 2004), (-)-xanthatin strongly up-regulated the expression of the RhoB isoform in a NAC-sensitive manner. We summarized the anti-proliferative effects of (-)-xanthatin in combination with our previous findings (Takeda et al, 2011(Takeda et al, , 2013a(Takeda et al, , 2013b) (See Fig. 3B).…”
Section: Introductionmentioning
confidence: 64%
See 2 more Smart Citations
“…1A, upper panel). To clarify the involvement of (-)-xanthatin in the extracts (Roussakis et al, 1994;Ramírez-Erosa et al, 2007) and to understand the SL's action mechanism, we have established a method for the complete synthesis of (-)-xanthatin in order to obtain "pure" (-)-xanthatin (Matsuo et al, 2010;Matsumoto et al, 2013) and applied this SL to biochemical analyses focusing on its anti-proliferative effects on the MDA-MB-231 cell line (Takeda et al, 2011(Takeda et al, , 2013a(Takeda et al, , 2013b(Takeda et al, , 2015, a model of basal-like triple negative (i.e., estrogen receptor α, progesterone receptor, and HER2/ ErbB2 negative) highly aggressive breast cancer (Roche-fort et al, 2003): the findings of that study indicated that the inhibition of (-)-xanthatin-mediated DNA topoisomerase IIα (Topo IIα) and production of reactive oxygen species (ROS) are involved in its anti-proliferative effects through the up-regulation of GADD45γ, an tumor suppressor gene (Ying et al, 2005;Zerbini and Liebermann, 2005). Although we and others have demonstrated the anti-proliferative effects of (-)-xanthatin on MDA-MB-231 cells (Ramírez-Erosa et al, 2007;Takeda et al, 2011, 2013a, 2013b: Yu et al, 2015, the molecular mechanisms underlying (-)-xanthatin-induced anti-proliferative activity have not yet been elucidated in detail.…”
Section: Introductionmentioning
confidence: 99%